Evaluasi Tata Kelola Teknologi Informasi pada Proses Pengelolaan Inovasi dan Pengelolaan Perubahan Teknologi Informasi Menggunakan COBIT 2019 di PT. XYZ: Evaluation of Information Technology Governance in the Innovation Management Process and Management Information Technology Change Using COBIT 2019 at PT. XYZ - Muhammad Ikhsan; Dinar Mutiara Kusumo Nugraheni (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
The development of information technology (IT) is a major factor in driving the business transformation process in an organization. To drive the business transformation process, good IT governance is essential, so that the utilization of IT in organizational functions can run optimally. This study aims to measure the level of IT governance capability at PT.XYZ. The IT governance audit conducted in this study used the COBIT 2019 framework in mapping the process to be assessed. In the design factor results, it is found that there are 2 domain processes that have a value above 75%, namely APO04 and BAI06 which are then obtained in the process of measuring the capability of each level, namely APO04 has a capability value at level 1, and BAI06 has a level 1 capability value. carried out the results of the gap analysis and obtained an average value of the gap of 3, that PT.XYZ needs to improve IT governance and management in order to achieve organizational goals. Based on these improvements, several recommendations are given for improvements that can be made by the company.